2016
DOI: 10.1186/s13024-016-0140-1
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 at the interface of autophagosomes, endosomes and lysosomes

Abstract: Over the past 20 years, substantial progress has been made in identifying the underlying genetics of Parkinson’s disease (PD). Of the known genes, LRRK2 is a major genetic contributor to PD. However, the exact function of LRRK2 remains to be elucidated. In this review, we discuss how familial forms of PD have led us to hypothesize that alterations in endomembrane trafficking play a role in the pathobiology of PD. We will discuss the major observations that have been made to elucidate the role of LRRK2 in parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 103 publications
2
134
0
1
Order By: Relevance
“…LRRK2 also contains protein scaffolding domains, including N‐terminal armadillo, ankyrin, and leucine‐rich repeat domains and a C‐terminal WD40 domain. LRRK2 has also been implicated in membrane dynamics in multiple organelles, including the trans‐Golgi network, endosomes, lysosomes, and autophagosomes, as well as synaptic vesicle recycling . In addition, mutant LRRK2 disrupts synaptic transmission in vivo .…”
Section: Genes Implicated In Pd That Play a Role At The Presynaptic Tmentioning
confidence: 99%
“…LRRK2 also contains protein scaffolding domains, including N‐terminal armadillo, ankyrin, and leucine‐rich repeat domains and a C‐terminal WD40 domain. LRRK2 has also been implicated in membrane dynamics in multiple organelles, including the trans‐Golgi network, endosomes, lysosomes, and autophagosomes, as well as synaptic vesicle recycling . In addition, mutant LRRK2 disrupts synaptic transmission in vivo .…”
Section: Genes Implicated In Pd That Play a Role At The Presynaptic Tmentioning
confidence: 99%
“…Although the exact function of LRRK2 remains to be elucidated, a role for LRRK2 in vesicular dynamics came from subcellular localization studies, which showed the localization of LRRK2 with endosomes, lysosomes and MVBs in the rodent brain and with the punctate, vesicular structures in human brain (Roosen and Cookson 2016). Further studies using cellular and animal models have suggested that the mutant forms of LRRK2 decrease LC3 lipidation and result in the accumulation of autophagic vacuoles (Roosen and Cookson 2016). In addition, LRRK2 was shown to interact with a number of Rab GTPases, including Rab7, Rab32 and Rab38 (Waschbusch et al 2014).…”
Section: Membrane Trafficking Defect In Parkinson's Diseasementioning
confidence: 99%
“…Last, idiopathic PD without LRRK2 mutations (PD+ LRRK2 ‐) offers an attractive treatment group to circumvent the challenges mentioned above. Scientifically, this group could also be rationalized on the basis of the potential role of LRRK2 in idiopathic PD pathogenesis (reviewed by Roosen and Cookson, 2016). However, idiopathic PD represents highly heterogeneous pathogenic mechanisms.…”
mentioning
confidence: 99%